The Impact of Environmental, Social, Governance, and Sustainability Committee Disclosure on Corporate Value and Reputation - Esteti Handayani Hia; Juniati Gunawan (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure and the Sustainability Committee on company value and reputation. The data used in this study is secondary data sourced from annual reports and the official website of the Bumi Global Karbon (BGK) Foundation for non-financial sector companies during the period 2020-2022. The research sample was selected using purposive sampling, resulting in 69 companies as the sample. The data analysis used for hypothesis testing was panel data regression analysis using the Eviews 12 program. The results of the study indicate that social performance disclosure has a positive effect on company value. The results also show that governance performance disclosure has a positive effect on company reputation. The findings of this study provide information that social performance and governance performance play an important role in enhancing company value and reputation. The level of a company's concern for sustainability is one of the considerations for investors when making investment decisions.